Recombinant, B-domain Deleted Factor VIII (r-VIII SQ): Pharmacokinetics and Initial Safety Aspects in Hemophilia A Patients - Fijnvandraat, K; Berntorp, E; ten Cate, J W; Johnsson, H; Peters, M; Savidge, G; Tengborn, L; Spira, J; Stahl, C (Thrombosis and Haemostasis, 1997)
The pharmacokinetics of a second-generation recombinant B-domain deleted factor VIII (FVIII) preparation (r-VIII SQ) were studied in 36 patients with severe hemophilia A. In contrast to full-length recombinant FVIII, no albumin needs to be added to stabilize the final formulation of this B-domain deleted FVIII preparation.The in vivo recovery and half-life of r-VIII SQ were similar to those of plasma-derived (pd) FVIII (mean half-life of r-VIII SQ, 11.7 h). The volume of distribution and clearance were slightly, but significantly, higher for r-VIII SQ than for pdFVIII (p<0.05). Peak plasma levels of FVIII were consistently related to the administered dose of r-VIII SQ (r = 0.94, p<0.0001). The pharmacokinetic profile of r-VIII SQ remained essentially unchanged in a dose range of 25-100 IU/kg body weight and could be reproduced after repeated doses. r-VIII SQ was well tolerated.In conclusion, deletion of the B-domain of FVIII does not influence its in vivo pharmacokinetics.